Examinations of impacts of empowering leadership on innovation activities in service sector and employees - Adıgüzel, Zafer; Cayan, Yeliz (Mehmet Akif Ersoy University, 2020)
The organizations in service sector in intense competition environment fall behind as a result of not showing performance in desired level and have to leave from the sector. In terms of leadership styles, it is necessary to manage the satisfaction and team management with the right understanding in the superior-subordinate relationship hierarchy of the organizations. By managing and guiding employees correctly, organizations can achieve their goals that they set. The research model examines how institutions in the service sector affect employees and innovation through the empowering influence of leadership. When the findings are analyzed, it was found that empowering leadership and proactive personality variables had positive effects on career satisfaction, innovation and creativity activities. Within the scope of the study, survey were conducted with 483 white-collar employees (administrative personnel) who work in the service sector (banking sector). SPSS 25 Program was used to make analysis. Since there were 5-point Likert-scale questions in the study, factor analysis was conducted. After factor analysis, reliability analysis, correlation analysis, regression analysis, and sobel test and hayes process were made for the analysis of mediation variable effect.

Yoğun rekabet ortamında hizmet sektöründe bulunan kurumlar istenilen seviyedeperformans sergileyememeleri sonucunda yarışta geriye düşmekte ve sektörden çıkmakzorunda kalmaktadırlar. Özellikle liderlik açısından örgütlerin ast-üst hiyerarşisindememnuniyet ve ekip yönetiminin doğru bir anlayışla yönetilmesi gerekmektedir.Çalışanların doğru yönetilmesi ve yönlendirilmesiyle, örgütler belirledikleri hedeflereulaşmaları mümkün olabilmektedir. Hizmet sektöründe bulunan kurumların, liderliğingüçlendirici etkisiyle çalışanları ve yeniliği nasıl etkilediği araştırma modelikapsamında incelenmektedir. Elde edilen bulgular analiz edildiğinde, Güçlendiriciliderlik ve proaktif kişilik değişkenlerinin, kariyer memnuniyetine, takım yaratıcılığınave yenilik faaliyetlerine olumlu yönde etkisinin olduğu tespit edilmiştir. Araştırmanınamacı kapsamında hizmet sektöründe (bankacılık sektöründe) bulunan 483 beyaz yakalı(idari personel)’dan veriler toplanmıştır. SPSS 25 Programı kullanılarak Analizleryapılmıştır. Anket çalışmasında 5’li Likert ölçekli sorular olduğu için faktör analiziyapılmış, faktör analizinden sonra güvenirlilik analizi, korelasyon analizi, regresyonanalizi, ve aracı değişken etkisi için sobel testi ve hayes process yapılmıştır.
Güçlendirici liderliğin, hizmet sektöründeki yenilik faaliyetlerine ve çalışanlara etkilerinin incelenmesi
Keywords: Proactive Personality; Service Innovation; Career Satisfaction; Empowering Leadership; Team Creativity; Proaktif Kişilik; Hizmet Yeniliği; Kariyer Memnuniyeti; Güçlendirici Liderlik; Takım Yaratıcılığı